(untitled) (Proceedings of the International Conference on Future of Women, 2018)
In the Sri Lankan setting, there is a long bounden connection between foreign direct investment (FDI) and financial development rate. The FDI dropped 54% to 450 million of every 2016 year-on-year, contrasted and 970 million in the earlier year. Sri Lanka wants to be the most famous nation for FDI by 2018 with financial development estimated at 7% in the coming years. One of the significant zones for such venture is believed to be tourism. Tourism is an incredible open door for financial improvement and neediness lightening in creating nations. The tourism industry is a standout amongst the most potential territories for outside speculation and development. Ladies’ work in tourism industry stays low under 8 percent for the main lodging networks in the nation and there are fears that this capacity for development might be decelerated by a genuine shortage in human resources especially. In a setting when ladies have break even with access to training and in fact are moving in huge numbers and generally utilized in numerous segments, and this exploration investigates why ladies’ work in the tourism industry in Sri Lanka is at such low levels? This exploration centers the inescapability of social hindrances to ladies’ work in the tourism industry, through a contextual analysis of one of Sri Lanka’s most seasoned resort tourism industry and meetings with senior industry experts. This was a cross sectional descriptive study with 11 women respondents who’re still working in the Heritance Ahungalla (HA) in the Southern region and the decisions a little example of five ladies who lived and worked near the exploration site, i.e. Heritance Ahungalla, were additionally met as the sample. The samples were selected purposively on the basis of inclusion and exclusion criteria. A semi structured questionnaire was used to collect data and consent was taken a prior interview. The investigation additionally worries to the idea of these hindrances: a) misperceptions b) preferences c) absence of mindfulness d) male centric dispositions and socio-social impacts e) contrasting levels of social estimation of various callings. The investigation features the part business and government can play in tending to these hindrances and to this end makes particular suggestions to extend ladies’ entrance and development inside the business.